(3TQM GdCOhjI GdeaQOI ef cJGH GdbGfhfs - (3SOjO GdOjf GdcGRQhfis; (3GdQFjS GHf SjfG , CHh Ydj TQa Gdedc (B: (3GdajdSha GdQFjS,J (B428 (3g` s
(3ChdgG (B:s
(3aEf gPG GdcJGH gh KGfi GdcJH GdJi UfafGgG ai GdWH GdChd efgG gh GdCMcGe s
(3BNQgG (B:s
(3eHJhQ GdGNQ(B: (3TLQI GdVQh hTLQg GdcecGe hGMOI ; adjMbb bhd GdTjN gh cGdChd ai GdbhI , hjONd ai WjH GdfSGA s
(3GdfSNI HgG MhGTs
(3TQM Ydi GdcJGH GdKGfi ef bGfhf GHf SjfGs
(3JHUQI GdYfhGf (B:s
(3TQMs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B2 - (3U (B241s
Keywords: (3GdWHs